مراجعة الجباية كمدخل لتفعيك التسيير الجبائي في المؤسسة الاقتصادية دراسة حالة بالمؤسسة الوطنية للدهن سوق اهراس - سهام، عباد; وداد معاوة (My University, 2018)
This study aims to highlight the role of tax audit which is one of the mechanisms that can improve the exercise of tax management, given their major importance in the organization, In addition, the tax audit allows an assessment of tax risks and to identify the strengths and weaknesses. weak points, in order to make the necessary decisions to avoid institutional penalties and fines incurred, putting the company in a favorable situation before the administration tax. This study concluded both in theory and in practice with the following results: • The review of taxation contributes to the improvement of tax management in institutions economical, providing flexibility in how to deal with tax laws characterized by continuous changes; • Requires the establishment of a management system within economic institutions that depends the management of a successful criminal and the need to train the human element, in particular people related to the field of accounting, auditing and collection. Keywords: tax audit, tax management, tax auditor, tax risk. ............................................................... تهدف هذه الدراسة إلى تسليط الضوء على دور التدقيق الضريبي الذي يعد أحد الآليات التي يمكن من خلالها تحقيق ذلك تحسين ممارسة إدارة الضرائب، نظرا لأهميتها الكبرى في المنظمة، بالإضافة إلى ذلك، يسمح التدقيق الضريبي بتقييم المخاطر الضريبية وتحديد نقاط القوة والضعف. نقاط الضعف، من أجل اتخاذ القرارات اللازمة لتجنب العقوبات المؤسسية و الغرامات المتكبدة، مما يضع الشركة في وضع مناسب أمام الإدارة ضريبة. وخلصت هذه الدراسة نظرياً وعملياً إلى النتائج التالية: • مراجعة الضرائب تساهم في تحسين إدارة الضرائب في المؤسسات اقتصادية، مما يوفر المرونة في كيفية التعامل مع القوانين الضريبية تتميز بالتغيرات المستمرة. • يتطلب إنشاء نظام إداري داخل المؤسسات الاقتصادية التي تعتمد عليها إدارة المجرم الناجح وضرورة تدريب العنصر البشري وخاصة الأشخاص المرتبطين بمجال المحاسبة والمراجعة والتحصيل.